A novel Co1.29Ni1.71O4/glycerolate-derived oxygen-vacancies-containing TiO2 composite for highly efficient photocatalytic hydrogen evolution. Issue 1 (February 2023) - Fang, Ningjie; Yan, Ping; Koide, Ryota; Shu, Song; Chu, Yinghao; Wang, Zhengming; Sano, Taizo
Abstract: Charge separation and migration is still a big challenge for photocatalysis. Constructing heterojunction interface structure is a useful way to improve charge separation efficiency. Here, a novel glycerolate-derived n-type TiO2 with oxygen vacancies was hybridized with Co1.29 Ni1.71 O4 by a facial ultrasonication method to achieve such a purpose. The optimized 2.5 % Co1.29 Ni1.71 O4 /TiO2 hybrid showed a photocatalytic hydrogen evolution rate of 1685 μmol g −1 h −1 under 365 nm LED light irradiation, 26.7-fold higher than that of pure TiO2 (63 μmol g −1 h −1 ). Besides, the hydrogen production amount kept a linear increase with the increase of irradiation time for the 2.5%Co1.29 Ni1.71 O4 /TiO2 catalyst during a 24 h-long continuous hydrogen release test, confirming the excellent catalytic stability. Detailed characterizations demonstrated that Co1.29 Ni1.71 O4 nanosheet was closely contacted with TiO2 nanoparticles, which increases specific surface area and widens the light absorption window of TiO2 . Moreover, Co1.29 Ni1.71 O4 addition facilitated highly efficient separation of photogenerated carriers and prolongs lifetimes of the excited electrons. First principles calculations confirmed that there existed strong interaction between Co1.29 Ni1.71 O4 and TiO2 in the composite, and electrons were directly transferred from Co1.29 Ni1.71 O4 to TiO2 at the interface by the Ni-O and Co-O pathway. All of these leaded to a high photocatalytic hydrogen evolution activity for the Co1.29 Ni1.71 O4 /TiO2 composite. This work revealed Co1.29 Ni1.71 O4 to be a promising heterojunction counterpart material and able to promote photocatalysis through unique cross-boundary charge transfer. Highlights: Co1.29 Ni1.71 O4 /glycerolate-derived-TiO2 p-n heterojunction composite was successfully synthesized. Ni and Co in the Co1.29 Ni1.71 O4 effectively transfer electrons to TiO2 at the interface. H2 O is preferentially adsorbed and dissociated at the interface. The HER activity was significantly enhanced by Co1.29 Ni1.71 O4 addition.